Performance of new generation pole light - Foo K.C.; Karunanithi S.; Thio G. (Institute of Physics Publishing, 2023)
This paper describes the design and implementation of a standalone photovoltaic power supply which caters for garden lighting scheme. New Generation Pole Light (NGPL) consists of three parts which are light dependent resistor (LDR) and pyroelectric infrared (PIR) sensors, microcontroller and light emitting diode (LED) and finally, solar charging system. During the night, LED is switched on with two operating modes which are ultra-bright lighting for a predetermine period (when human presence is detected) and dim lighting. Meanwhile, LED is switched off at day time and solar charging system will recover the capacity of discharged battery. NGPL provides portable, sustainable, environmental friendly and requires minimal maintenance for outdoor lighting scheme for both urban and rural areas. Published under licence by IOP Publishing Ltd.